STRATEGI KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN PENDEKATAN PEMBELAJARAN MENDALAM DI SEKOLAH DASAR - Sasmita, Cici; Yantoro; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze school principals' strategies in implementing the Deep Learning approach in three Public Elementary Schools in Jambi City. Using a qualitative approach with a multiple case study design, data were collected through in-depth interviews with school principals, participant observation, and documentation studies at SDN 42/IV, SDN 64/IV, and SDN 54/IV Jambi City. The results reveal variations in the implementation strategies developed by each school. SDN 42/IV applied a structured, collaboration-based approach through the formation of a curriculum development team. SDN 64/IV developed a technology innovation strategy through the transformation of digital infrastructure and intensive teacher training. Meanwhile, SDN 54/IV emphasized the strengthening of learning communities through the establishment of a Professional Learning Community (PLC). The key findings indicate that the success of implementation is influenced by three main factors: the commitment of the principal's instructional leadership, continuous teacher capacity building, and the creation of a conducive learning environment. This study makes an important contribution to the development of an effective school leadership model for implementing Deep Learning, while also serving as a reference for policymakers in formulating contextual implementation strategies for educational innovation at the elementary school level.